Socioemotional Challenges of Indigenous Elders: A Study Based on a Rural Village in Northern Sri Lanka - Jeevasuthan, S.; Jeyaruban, V. (Oxford University Press, 2023)
The internal conflict that has occurred during the past 30 years in northern Sri Lanka has led to disruption in the traditional family structure. In one of the villages in northern Sri Lanka, a research study was conducted to learn about the effects on Indigenous older persons of the years of conflict, departure of younger people away from the land, and subsequent changes to the lives of older persons left on their own without the customary care provided by their family members. The caste system is still a factor in the study area. Customarily, care provided by lower caste persons for higher caste older persons was not socially accepted. However, higher caste older persons, many of whom reported health and mental health and mobility challenges, have remained on their land and in their homes without family care. They have found ways to adapt to their situations due to necessity and secured help from lower caste workers. As this chapter discusses, the study found that paid caregivers provide much useful instrumental help for older persons, such as running errands and helping facilitate communication with older persons’ distant family members. Such arrangements have become more common in the study area for this higher income cohort of older persons because the older population in the study area tended not to consider institutional residential settings to receive care due to negative perceptions and the view that they were a last resort.
Keywords: Upper middle-class elders; Displacement; Socioemotional challenges; Quality care; Sri Lanka